Continuation of Mr Macdonald’s Paper on Burghead, from Part I. Vol. IV of the Proceedings - MacDonald, James (Proceedings of the Society of Antiquaries of Scotland, 1862)
Using Roy’s map of the area and accounts written since the map was produced, James MacDonald continues his analysis of the historical significance of the structures at Burghead. He recounts the findings of the excavations that took place at Burghead in the nineteenth century and provides the dimensions of each part of the site he discusses. Included in the paper are comments on some of the artefacts found at Burghead, such as carved stones, a medieval metal jug and accounts of human remains unearthed in 1809. After examining the evidence, the author concludes that it is unlikely that the fort was constructed by the Romans, but instead suggests that it was built at a later date in the early medieval period, possibly by the Picts.